หลักการบริหารต่อรัฐตามคำภีร์พระพุทธศาสนา - อนนท์จารย์, สุขพัฒน์ (วารสารศรีล้านช้างปริทรรศน์; Vol 2 No 2 (2016): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 2 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2559), 2016)
หลักการบริหารต่อรัฐที่มีมาตั้งแต่สมัยก่อนพุทธกาล ก่อนที่พระพุทธเจ้าจะเสด็จอุบัติขึ้นบนโลกนี้ เมื่อพระพุทธศาสนาได้ก่อตั้งเป็นที่เรียบร้อยแล้ว พระพุทธเจ้าก็ได้นำเสนอรูปแบบการปกครองรูปแบบใหม่ โดยพระองค์ได้นำไปใช้กับคณะสงฆ์เป็นกลุ่มแรก นับว่าเป็นรูปแบบหนึ่งที่ดีที่สุดเท่าที่เคยมีมาบนโลกใบนี้ กล่าวคือ รูปแบบการปกครองระบบธรรมาธิปไตย เป็นรูปแบบหนึ่งที่ชาวโลกเข้าถึงได้ยากมาก เพราะยึดหลักคุณธรรม หากคนในรัฐเป็นคนดี จะเป็นระบบเผด็จการหากได้คนดีเป็นผู้นำก็เป็นธรรมาธิปไตยได้ ระบบประชาธิปไตยหากกลุ่มชนไม่ดีเป็นแกนนำก็เป็นธรรมาธิปไตยไม่ได้ เพราะฉะนั้นชุดความคิดในทางพระพุทธศาสนา ขึ้นอยู่กับตัวปัจเจกชนเป็นสำคัญหากคนเราเป็นคนดีแล้วจะนำพาทุกอย่างดีไปหมด ตัวแปรที่สำคัญอยู่ที่ตัวมนุษย์เป็นสำคัญ ดังนั้น พระพุทธศาสนาจึงมุ่งสร้างมนุษย์ให้เป็นคนดี โดยสร้างเกณฑ์ตัดสินคนดีขึ้นเพื่อเป็นตัวชี้วัด และชี้แนวทางแห่งการเข้าถึงความดีในแต่ละดับขึ้น           การบริหารรัฐแบบราชาธิปไตย หรือแบบอัตตาธิปไตย หรือว่าแบบเผด็จการในปัจจุบัน ก็คือระบบเดียวกัน โดยอำนาจในอยู่มือบุคคลคนเดียว หากได้คนดีมีคุณธรรมก็จะนำพารัฐเจริญรุ่งเรือง ให้ชนในรัฐอยู่เย็นเป็นสุข ในทางกลับกันหากได้ผู้นำเป็นคนไม่ดีไร้คุณธรรม ก็จะนำพารัฐไปสู่ความหายนะทันตาเห็นได้เช่นกัน           การบริหารรัฐแบบสามัคคีธรรม หรือแบบคณาธิปไตย หรือว่าแบบประชาธิปไตย มีคนหลายคนมีส่วนร่วม ช่วยคิดช่วยทำขับเคลื่อนไปด้วยกัน ถ้าหากได้กลุ่มแกนนำเป็นคนดีมีศีลธรรม พัฒนาการทางภาครัฐก็จะไปได้สวย เจริญรุ่งเรื่องในทุกๆ ด้านเป็นอย่างดี ลดความผิดพลาดได้ดีเพราะมีหลายคนช่วยกรองงาน แต่ในทางตรงกันข้ามหากได้กลุ่มแกนนำไม่ดี ความผิดพลาดใหญ่ก็จะตามมาเช่นกัน           จะเห็นได้ว่า ระบบธรรมาธิปไตยนับว่าเป็นระบบที่สมบูรณ์ที่สุด ที่ชาวโลกส่วนใหญ่คาดหวังอยากจะได้              The public governance in Ancient India was found existing before the Buddha’s lifetime or before the Buddha appeared in the world. After Buddhism was successfully founded, the Buddha announced a new formation of governance, which was initially used to govern the ecclesiastical council of Buddhist monks. It was regarded as one of the best formations of governance in the world. Based on supremacy of righteousness, such a formation of governance was found to be difficult for people to understand because it was attached to the principle of morality. If the leader of the state was a good man, the government was on the supremacy of righteousness or democracy. In case the state leaders were not good, the government was inevitably under totalitarianism or dictatorship, not on righteous governance. Therefore, the mind set in Buddhism was distinctly dependent upon an individual. If a man was good, everything would be good as well. As said, a man was held as an important variable. So, Buddhism was aimed to develop a good man under certain indicators as a criterion for a good man. Nevertheless, there was also a way to access each level of good, proclaimed by the Buddha.           Monarchy or self-dependence (the supremacy of self), including the present dictatorship, was regarded as the same system because the state sovereignty was under one person. If the leader was righteous, the state prosperity and the well-being of people in the state were expected. Conversely, if the leader was without righteousness, he was promptly believed to lead the state to disaster.           The state administration of fellowship, either oligarchy or democracy, was participated with several people to co-operate the state. In case the leader group were good with virtue, the state would be developed and prospered in all aspects and the failure of the state administration would decrease under the scrutinization of many people. Contrastingly, if the leader group were wicked, the big mistakes would increase.            As seen, the supremacy of righteousness was regarded as the most perfect government expected by the majority of people in the world.